The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5530/pj.2018.4.108
|View full text |Cite
|
Sign up to set email alerts
|

An Interactive Antimicrobial Activity of Embelica officinalis Gaertn. Fruit Extracts and Conventional Antibiotics against Some Bacterial Triggers of Autoimmune Inflammatory Diseases

Abstract: Background: Embelica officinalis Gaertn. is an Indian plant which is known for its therapeutic properties. It is especially well known as a component of the Ayuverdic medicine Triphala. This study focuses on the growth inhibitory activity of E. officinalis fruit extracts against some bacterial triggers of autoimmune inflammatory diseases, both alone and in combination with conventional antibiotics. Methods: E. officinalis fruit powder was extracted with solvents of varying polarity and screened for bacterial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 19 publications
(29 reference statements)
1
22
0
Order By: Relevance
“…antibiotics that are otherwise ineffective against resistant bacterial strains. Several studies investigating combinations of conventional antimicrobialswith African, [3][4] Asian [5][6] and Australian traditional medicinal plants 7 have recently been published, highlighting the increased efficacy of some combinational antibiotic therapies. Several of these studies have identified plant extracts which synergistically enhance the activity of conventional antimicrobials, even when the plant extracts do not possess antimicrobial activity in isolation.…”
Section: Interactive Antimicrobial and Toxicity Profiles Of Scaevola mentioning
confidence: 99%
“…antibiotics that are otherwise ineffective against resistant bacterial strains. Several studies investigating combinations of conventional antimicrobialswith African, [3][4] Asian [5][6] and Australian traditional medicinal plants 7 have recently been published, highlighting the increased efficacy of some combinational antibiotic therapies. Several of these studies have identified plant extracts which synergistically enhance the activity of conventional antimicrobials, even when the plant extracts do not possess antimicrobial activity in isolation.…”
Section: Interactive Antimicrobial and Toxicity Profiles Of Scaevola mentioning
confidence: 99%
“…Interactions between the Astragalus root extracts and the conventional antibiotics were examined by determination of the sum of fractional inhibitory concentrations (ΣFIC) for each combination. 39 The FIC values for each component (a and b) were calculated using the following equations where a represents the plant extract sample and b represents the conventional antibiotic:…”
Section: Fractional Inhibitory Concentration (Fic) Assessmentmentioning
confidence: 99%
“…Combinational approaches may prove to be more effective in overcoming antibiotic resistance and may even allow conventional antibiotics to again be effective against resistant bacterial strains. Several studies have already investigated combinations of natural product and conventional antimicrobials and have reported promising results [3][4][5][6][7][8][9]. Several plant species have been identified that substantially potentiate the activity of conventional antimicrobials, even when the plants do not possess antimicrobial activity alone [2,3,8].…”
Section: Introductionmentioning
confidence: 99%